Striving for Better Jobs : The Challenge of Informality in the Middle East and North Africa - Gatti, Roberta; Angel-Urdinola, Diego F.; Silva, Joana; Bodor, Andras (World Bank, Washington, DC, 2014)
Economic growth has been sustained for many years pre-crisis in the region, but this has not resulted in the creation of an adequate number of jobs and has succeeded, at best, in generating low-quality, informal jobs. The report addresses one margin of exclusion: informal employment and the vulnerabilities and lack of opportunities associated with it. The report analyzes the constraints that prevent informal workers from becoming formal and discusses policy options to effectively address these constraints. This report looks at informality through a human development angle and focuses particularly on informal employment. Informality is a complex phenomenon, comprising unpaid workers and workers without social security or health insurance coverage, small or micro-firms that operate outside the regulatory framework and large registered firms that may partially evade corporate taxes and social security contributions. The first section provides a detailed profile of informal workers in the region. The second section describes the characteristics of informality in micro-firms that operate outside the regulatory framework and in larger firms that do not fully comply with social security contribution requirements and tax obligations. The third section presents informality and the firm. The fourth section focuses on informality: choice or exclusion? The fifth section discusses policy options for effectively expanding coverage of health insurance and pension systems and promoting the creation of better quality jobs.